The main deity of Belur- Sri Chennakeshava - Vanishree Mahesh (2021)
The main deity of Beluru Keshava is a male deity, he is dressed as a female here and is worshipped as Mohini. According to Puranas, Vishnu took the form of a beautiful maiden named Mohini to slay a demon named Bhasmasura. The Mohini-Bhasmasura event is believed to have taken place at the premises of the Belur temple.